Phase a nal ysis and m icrostructure s tudy of s intered Ni-Crc omposites containing MoS2, Ag and CaF2additives as solid l ubricants - Mohamad, W.F. (Universiti Malaysia Pahang, 2020)
Ni-Cr based composites with and without the addition of solid lubricants (MoS2, Ag and CaF2) were prepared by powder metallurgy method. The samples were sintered at different temperatures (1000oC, 1100oC and 1200oC) under controlled atmosphere and various holding times. The physical properties such as sintered density, relative density and porosity were studied. The microstructures and phase studies of the Ni-Cr based composites were conducted using Scanning Electron Microscope (SEM) and X-Ray Diffraction Analysis (XRD) while the hardness of the composites was measured by the Vickers Micro Hardness Tester. The results revealed that as the sintering temperature was increased, the sintered density, relative density and hardness also increased while the porosity was reduced. At the sintering temperature of 1200oC, the relative density reached its maximum value. SEM and XRD analysis confirmed the existence of MoS2 and Ag in sintered samples. MoS2 and Ag were not mainly dissolved and/or decomposed even after sintering at 1200oC. Â© The Authors 2020.